Landscape Filters of Functional Trait Diversity and Composition - Paradis, Anouk (Université d'Ottawa / University of Ottawa, 2020)
Human activities are altering species' environments, consequently driving many to extinction and changing biotic communities worldwide. Functional traits are species’ intrinsic characteristics that shape their roles in an environment. Loss of functional diversity compromises ecosystem processes and potentially the resilience of communities facing further change. Biological homogenization reflects the non-random loss of species and possibly also of trait distributions within community, leading to the increasing ubiquity of some traits and growing rarity of others. By changing the composition and configuration of species’ local habitat and their regional surroundings, land use can alter community dynamics. The extent to which land uses within habitats and across the surrounding landscape matrix alter the distribution of functional traits in biotic communities remains highly uncertain but could determine how to design management strategies intended to aid conservation. Here, I investigate the relative contributions of compositional and configurational landscape characteristics at local and regional scales on the diversity and composition of functional traits within butterfly communities. I constructed models to identify landscape predictors of functional trait diversity but found no significant associations with individual traits. Managing habitat quality by fostering compositional and configurational heterogeneity in the local landscape can improve functional diversity. However, efforts to facilitate conservation of species with rare traits necessitates maintaining compositional and configurational variety within habitats and in the surrounding matrix.
Keywords: Functional trait; Landscape filters